USING ELECTRONIC LANGUAGE GAMES TO DEVELOP LINGUISTIC SKILLS IN CHILDREN WITH SPECIAL NEEDS - Samira Ouazib (International Journal of Innovative Technologies in Social Science, 2025)
This study aims to highlight the importance of electronic language games in teaching children with special needs, equipping them with linguistic skills that help them express their needs, reduce the impact of their disabilities on communication with others, and enable them to integrate into their communities alongside their typically developing peers.